Lifelong learning for sustainable development – student’s perspective (Vallis Aurea, 2023)
Purpose – The purpose of this paper is to determine the knowledge, views and opinions of students about sustainable development and lifelong learning as a part of education for sustainable development. Design – The empirical part of the paper consists of the results of a primary research conducted among students of higher education institutions.Methodology - An online questionnaire was distributed among students using convenience and snowball sampling to select students from different backgrounds, who then completed standardized instruments. The research was conducted using the survey questionnaire technique. For analysing the data, descriptive statistics were used. Approach - Quantitative method of research.Findings -. Results of the empirical research on sustainable development and lifelong learning for sustainable development are presented. The research shows which learning outcomes, techniques and topics students found most valuable to achieve sustainable development.Originality of the research – There is a lot of research on sustainable development, education for sustainable development as well as lifelong learning but a very small number connects the all of the above.  This paper contributes to the discussion of the concept of education for sustainable development in the context of lifelong learning.